Organization actions quality estimation by the expert estimation method in complex information protection system - Пігур, Наталія Володимирівна; Погребенник, Володимир Дмитрович (Ukrainian Information Security Research Journal, 2013)
For complex information protection system creation it is necessary to use complex of actions on safety ensurance in three levels: legal, organizational and technical. On organization level there exists a lot of protection components, that leads to the necessity of their quality estimation. Organization actions quality estimation by the expert estimation method is important, because while setting some threshold (on which is possible to remove some actions) we can reduce their quantity, that will lead to expenses reduction, and also to system cost reduction. There was estimated organizational protection actions quality, there was given examples of this actions expert estimation in system creation process, it's preparing to exploitation and in process of system exploitation.